COMBINED PTERYGOID AND ZYGOMATIC IMPLANTS: ANALYSIS OF ANCHORAGE AND SINUS COMPLICATIONS - Marques, Diego César; Vitorino, Giordanna Bomfim; Fernandes, Lucas Giovanne Carlos Pinheiro; Martins, Lilian Figueiredo; Rodrigues, Graziele; Novy, Luiz Felipe Silva; Moscatiello, Rafael Muglia; Vitale, Marcelo; Santos, Thayná Roberta Dias; da Silva Júnior, José; Storck, Itamar Júnio Vilhena; Brandão, Flávio Eduardo; et al. (Seven Editora, 2025)
The rehabilitation of severely atrophic maxillae remains a relevant clinical challenge in implant dentistry, particularly when bone volume and density are insufficient for conventional implant placement. In this context, zygomatic and pterygoid implants have emerged as biomechanically stable alternatives capable of supporting immediate loading protocols and reducing the need for extensive bone grafting. This integrative review analyzed the scientific evidence published between 2015 and 2025 regarding the isolated or combined use of zygomatic and pterygoid implants in maxillary rehabilitation. A structured search was conducted in PubMed, SciELO, Scopus, and Web of Science using MeSH/DeCS controlled descriptors and Boolean operators. Twenty eligible studies were included after screening. The findings demonstrated high success rates (93–98%), strong primary stability, and clinical feasibility of immediate loading, particularly when both implant types were used synergistically. Reported sinus-related complications were low (3–6%) and predominantly resolved through conservative management. Methodological limitations were identified, including heterogeneity in study design, lack of standardization of clinical criteria, and short follow-up periods. Overall, the combined technique demonstrates high clinical predictability; however, further multicenter prospective trials and long-term investigations are required to establish standardized clinical protocols. DOI: https://doi.org/10.56238/sevened2025.037-046